Ambulatory Pessary Trial Unmasks Occult Stress Urinary Incontinence - Bilal Chughtai; Sara Spettel; Jonathan Kurman; Elise De (Obstetrics and Gynecology International)
Objective. We evaluated the use of a one-week ambulatory pessary trial in predicting patients' postoperative outcomes for occult stress incontinence. Methods. Patients with anterior vaginal wall prolapse were offered a pessary trial to predict response to reconstruction. We performed a retrospective review of 4 years of cases. All patients underwent a detailed evaluation including videourodynamics with and without pessary reduction. Results. Twenty-six patients completed the 1-week pessary trial. Ten (38%) women showing no evidence of stress urinary incontinence (SUI) underwent surgical repair of prolapse without anti-incontinence procedure. None of these patients had SUI postoperatively. Sixteen women (61%) had occult stress urinary incontinence on evaluation and underwent concurrent sling procedure. Three (19%) of these patients were identified by the pessary trial alone. Twenty-five of the 26 patients were without clinical stress incontinence at a mean follow up of 12 months (range 4–37 months). The pessary trial correctly predicted persistent urgency in six patients and persistent frequency in five. No patients with SUI or persistent voiding difficult were missed in a pessary trial. Conclusion. An ambulatory pessary trial is an effective, easy, and inexpensive method to approximate anatomic results achieved by surgery under real-life conditions. In our series, 20% of patients with occult SUI were identified by pessary trial alone.